The Grammatical Mistakes Found in the Movie Script of Bad Boys for Life (2020) - Paramitha, Radhina Pradnya; Juliansyah, Juliansyah; Adi, Bambang Trisno; Afiyati, Alia; Beresaby, Rheinatus Alfonsus (English Education and Literature Journal (E-Jou), 2025)
This study focuses on analysing the types of grammatical mistakes found in movie script of Bad Boys for Life (2020). The main data were obtained from the script of the movie and were analysed based on the conceptual framework of grammatical mistake theory. This research is using Descriptive Qualitative Method to analyze the grammatical mistakes of some sentences from the Bad Boys for Life movie script. The data (primary) of this research are all sentences in the Bad Boys for Life movie script. Not all sentences in the script are analysed but only the ones uttered by the main characters, namely Mike and Marcus. We do certain actions in order to gather the data. These include: (1) reading the screenplay, (2) spotting grammatical errors in the script, (3) compiling the sentences that contain grammatical errors, and 4) analyzing the errors, particularly in the area of grammar, by consulting any article sources. The grammatical mistakes found are categorized into 4 types. They are: 1) Missing the auxiliary verb, 2) Problems with the subject and verb agreement, 3) Problems with the pattern of question or interrogative sentence, and 4) Other kinds of error. The analysis of the error is done descriptively by citing related references. Totally, there are 69 errors but only 19 are discussed here.